2015
DOI: 10.1007/s13277-015-4299-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells as trigger to hematogenous spreads and potential biomarkers to predict the prognosis in ovarian cancer

Abstract: Despite several improvements in the surgical field and in the systemic treatment, ovarian cancer (OC) is still characterized by high recurrence rates and consequently poor survival. In OC, there is still a great lack of knowledge with regard to cancer behavior and mechanisms of recurrence, progression, and drug resistance. The OC metastatization process mostly occurs via intracoelomatic spread. Recent evidences show that tumor cells generate a favorable microenvironment consisting in T regulatory cells, T infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…They have been demonstrated to open a new research field in diagnosing, evaluating clinical effect, and monitoring recurrence in ovarian cancer [15]. Functional analysis of CTCs based on in vitro and in vivo models from breast, prostate and colon cancers have also attracted some interest due to the possibility of revealing the biological properties of metastatic cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…They have been demonstrated to open a new research field in diagnosing, evaluating clinical effect, and monitoring recurrence in ovarian cancer [15]. Functional analysis of CTCs based on in vitro and in vivo models from breast, prostate and colon cancers have also attracted some interest due to the possibility of revealing the biological properties of metastatic cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Different detection methods were used, mainly based on immunocytochemistry (microscopic detection or the FDA-approved CellSearch ® system), RT-PCR (AdnaTest, QIAGEN, Hilden, Germany), and RT-qPCR for the quantification of CTCs levels [20,21]. The time point of blood collection also differed, however, in the majority of studies the peripheral blood samples were obtained before surgical removal of the tumor.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…They found that 43 (60.6%) patients had detectable CTCs, including 0/5 benign patients, 1/10 (10%) early stage, 39/52 (73.1%) late stage, and 3/4 (75%) unstaged patients [ 54 ]. Unfortunately, the concentration of CTCs presented in OC are extremely low, 1/10 9 blood cells or 1/10 6 nucleated blood cells [ 2 ], and CTCs counts are not significantly associated with clinical characteristics or patient outcomes [ 50 ]. However, the presence of CTCs at diagnosis seems to be correlated with adverse clinicopathological features, and worse clinical outcome, in OC individuals [ 55 ] with elevated CA-125 and HE-4 levels [ 56 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Ovarian cancer (OC) is the fifth most common cause of cancer death and remains the most leading cause of gynecological death [ 1 ]. These poor outcomes are directly related to the fact that a large majority, almost 75% of ovarian cancers, are diagnosed at advanced stage (III/IV), when transperitoneal, hematogeneous, and lymphatic dissemination have already occurred [ 2 ]. In general, effective therapy in OC patients can achieve 90% when the tumor is still confined to the ovary; unfortunately, only 25% of OC can be diagnosed before it exacerbates [ 3 ].…”
Section: Introductionmentioning
confidence: 99%